Hand, foot and mouth disease: University Malaya Medical Centre experience - Hooi, P.S.; Chua, B.H.; Lee, C.S.M.; Lam, S.K.; Chua, K.B. (2002)
The prevalence of HFMD as well as the causative agents was unknown in peninsular Malaysia prior to May 1997. From May 1997 to June 2001, 585 patients suspected to have enterovirus infections, with 467 patients clinically diagnosed as having HFMD, were investigated in the diagnostic virology unit of the University Malaya Medical Centre. Data from this study showed that HFMD is endemic in Malaysia with the occurrence of two outbreaks during the study period. In each outbreak, a number of viruses were isolated but enterovirus 71 was the man virus isolated in both outbreaks. Echovirus 7 (Eo7) was isolated from 5 patients with HFMD in the second outbreak, a clinical entity that has not been attributed to it previously. Children aged 4 years and below, particularly those between 1 and 2 years of age, were in the main group of patients affected by the illness. HFMD by itself and without neurological involvement was relatively benign and self-limiting. There was no significant difference in the virus isolation rate with respect to gender and ethnic groups. Virus isolation was attempted in a total of 764 clinical specimens consisting of 342 stool specimens, 285 oral secretions specimens and 137 vesicular fluid specimens. Oral specimens gave the highest virus isolation rate (33.3%) followed by vesicular specimens (27.0%). Stool specimens only yielded an isolation rate of 14.0%.